Mengembangkan Kemampuan Motorik Halus Anak Menggunakan Kombinasi Model Pbl Model Explicit Instruction Melalui Permainan Tradisional Dakuan Di Kelompok B TK Negeri Pembina Banjarmasin Timur - Fradya Auriani; Mohammad Dani Wahyudi (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The purpose of this study was to describe teacher activities, analyze children's activities, and analyze the results of children's fine motor skill development. This study used a qualitative approach with Classroom Action Research (CAR) conducted over four meetings. The subjects were 15 children in Group B at Pembina State Kindergarten, East Banjarmasin. The results showed that teacher activities were in the “Very Good” category with a score of 26. Children's activities were in the “Very Active” category with a score of 100%. The results of children's fine motor development were in the "Very Well Developed" category with a score of 100%.